Analysis of User’s Behaviour on Used and Waste Mobile Phone Recycling: An Intention to Natural Resource Management - M. G. , Prasanna Kumar; Raju, Y. M. (Gyan Management Journal, 2016)
The aim of this paper is to investigate the behaviour of user’s towards Used and Waste mobile p recycling on a national scale in India. With this goal in mind, a questionnaire survey was perform a large scale to explore user’s behaviours, and attitudes for recycling used mobile phones. There 680 effective questionnaires, were distributed and collected among Tier-JI cities of Karnataka and the questionnaire was analysed with percentage analysis. Therefore, mobile phone producers the government should mostly share the responsibility of waste mobile phone recycling.